Experimental design, modeling and optimization of polyplex formation between DNA oligonucleotides and branched polyethylenimine1. Issue 36 (28th September 2015) - Clima, Lilia; Ursu, Elena L.; Cojocaru, Corneliu; Rotaru, Alexandru; Barboiu, Mihail; Pinteala, Mariana
<x xml:space="preserve">Abstract</x> The complexes formed by DNA and polycations have received great attention owing to their potential application in gene therapy.